Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.jmig.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted Extraperitoneal Para-aortic Lymphadenectomy Is Associated with Fewer Surgical Complications: A Post Hoc Analysis of the STELLA-2 Randomized Trial

Abstract: Study Objective: To evaluate if extraperitoneal para-aortic lymphadenectomy (PALND) using a robot-assisted approach was associated with fewer complications than all other approaches (conventional laparoscopic transperitoneal or extraperitoneal and robot-assisted transperitoneal) without compromising lymph node yield, operative time, or length of stay. Design: Post hoc analysis of the prospective randomized open-label multicenter trial (STELLA-2). Setting: Three academic referral hospitals. Patients: Two hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…When we pooled the results from the seven studies, the EP group demonstrated less PALND operative time compared to TP (WMD −10.46 min, 95% CI −19.04, −1.88; p = 0.02) (20,21,24,25,27,28,30). However, the sensitivity analysis showed no significant differences with the removal of two studies (23,26) (p = 0.16, p = 0.10).…”
Section: Outcome Analysis Perioperative Outcomesmentioning
confidence: 92%
See 2 more Smart Citations
“…When we pooled the results from the seven studies, the EP group demonstrated less PALND operative time compared to TP (WMD −10.46 min, 95% CI −19.04, −1.88; p = 0.02) (20,21,24,25,27,28,30). However, the sensitivity analysis showed no significant differences with the removal of two studies (23,26) (p = 0.16, p = 0.10).…”
Section: Outcome Analysis Perioperative Outcomesmentioning
confidence: 92%
“…According to the literature search and the inclusion criteria, we included 2,354 patients in 13 studies (3 RCTs and 10 non-RCTs) for meta-analysis (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The 10 non-RCTs were all the retrospective comparisons (Figure 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, most of them concerned vascular injuries during lymphadenectomy that were managed by suturing, coagulation or surgical clip placement. Same statement was published in a large prospective randomized trial [6]. Bebia et al concluded that robotic assisted lymphadenectomy is associated with fewer complications compared to laparoscopic, due to better visualization, surgeon's ergonomy and hemostatic precision [6].…”
mentioning
confidence: 93%
“…Same statement was published in a large prospective randomized trial [6]. Bebia et al concluded that robotic assisted lymphadenectomy is associated with fewer complications compared to laparoscopic, due to better visualization, surgeon's ergonomy and hemostatic precision [6]. Based on their findings, do the authors have a similar experience?…”
mentioning
confidence: 95%